Periodismo digital y Facebook durante el COVID-19 en Perú y Ecuador (Monográficos) - Márquez Domínguez, Carmelo (2021)
El Comercio in Ecuador and in Peru are considered two reference media with significant audiences. Both, although their names correspond, use different speeches when it comes to issuing information according to the characteristics of their users, who differ when interacting with content on various topics. The pandemic around COVID-19 changed coverage routines. Both newspapers focused a large part of their publications on exposing information about the virus and the reactions of each government. The objective of this study was to identify the components of the journalistic discourse with the greatest relevance, about the pandemic, exposed by both media from the first cases of COVID-19 in Peru and Ecuador, as well as to determine the reactions of the audiences accordingly. of interactions with the content presented. The approach was qualitative from a case study. The techniques applied for data collection were observation and metric analysis. Among the main results is an eminently informative discourse, although with certain sensational doses, suggesting that, as reference media, they respond to journalistic practices that seek to approach the objectivity of the various issues, even in times of pandemic.